Investigating the Effects of Socioscientific Issues-based Learning Module in Enhancing Students’ Physics Knowledge - Jeah May Badeo; Bee Ching Ong Kian Koc; Domarth Ace G. Duque; Russel L. Arnaldo (Science Education International)
This study investigated the effect of using socioscientific issues (SSI)-based learning modules in enhancing physics knowledge. Three SSI-based learning modules were developed in this study and obtained a “Very Satisfactory” rating after the expert’s evaluation, electromagnetic (EM) waves module (M = 3.82, standard deviation [SD] = 0.13), applications and uses of EM waves module (M = 3.81, SD = 0.08), and Images Formed in Plane and Spherical Mirrors module (M = 3.84, SD = 0.08). A mixed-methods approach using a purposive one-group pre-test–post-test design was used to investigate the use of SSI-based modules in class. Participants of this study were Grade 10 students in a public school in Manila City, Philippines, selected using purposive sampling, with corresponding parental consent. Quantitative data obtained from the 35-item researcher-made physics test were analyzed using a paired-sample t-test, and qualitative data were gathered from student interviews. After the use of SSI-based learning modules for 4 months, a significant change was revealed in students’ physics knowledge as shown in the difference between the pre-test and post-test scores for Module 1(t(46) = 12.18, p < 0.05), Module 2 (t(46) = 15.08, p < 0.05), and Module 3 (t(46) = 24.27, p < 0.05). The yielded effect sizes for this analysis were 0.67 for Module 1, 0.72 for Module 2, and 0.80 for Module 3, which indicates that there were medium effects on students’ knowledge in Modules 1 and 2, whereas a large effect in Module 3. Results of this study showed that the implementation of SSI-based learning modules increases physics knowledge, which led students to explore the connection of the SSI to the presented physics topics. Future research may carry out the study on a larger scale with a control and experimental group.